Entwined - Dixon, Heather (New York : Greenwillow Books, 2011)
Confined to their dreary castle while mourning their mother's death, Princess Azalea and her eleven sisters join The Keeper, who is trapped in a magic passageway, in a nightly dance that soon becomes nightmarish.
Keywords: Princesses -- Fiction; Dance -- Fiction; Magic -- Fiction; Kings, queens, rulers, etc. -- Fiction; Fathers and daughters -- Fiction; Death -- Fiction; Fantasy